Analisis Kepuasan Petani terhadap Penggunaan Benih Jagung Pipil Bersertifikat di Desa Pasaranom, Kabupaten Purworejo - Anjani, Jessica Dewi; Kusumo, Rani Andriani Budi (Universitas Galuh, 2026)
All farmers in Pasaranom Village, Purworejo Regency, have used certified shelled corn seeds in their farming activities. However, the productivity level achieved is still not ideal, necessitating an evaluation of farmers satisfaction and identification of priority attributes for improvement. This study aims to analyze the level of farmer satisfaction and assess the importance and performance of each attribute of certified shelled corn seeds in Pasaranom Village. This quantitative research employs a survey technique. Respondents are shelled corn farmers in Pasaranom Village who have planted certified seeds at least three times and were selected using proportional random sampling. Primary data were collected through a Likert scale (1–5) questionnaire and analyzed using the Customer Satisfaction Index (CSI) to measure satisfaction levels and the Importance Performance Analysis (IPA) to determine the importance and performance levels. Secondary data were gathered from literature studies including books and journals. The results indicated that farmers’ satisfaction falls into the moderately satisfied category with a CSI value of 63.34%. Based on IPA analysis, four attributes were identified as priorities for improvement: seed brand quality consistency, resistance to pests and diseases, productivity in line with product claims, and selling price that meets farmers’ expectations. These findings indicate that further enhancement of seed quality and resistance is necessary to optimize the economic benefits gained from the use of certified shelled corn seeds.